Primary frequency H∞ control in stand-alone microgrids with storage units: A robustness analysis confirmed by real-time experiments. (February 2020) - Lam, Quang Linh; Bratcu, Antoneta Iuliana; Riu, Delphine; Boudinet, Cédric; Labonne, Antoine; Thomas, Martin
Highlights: An H ∞ primary frequency control is proposed for a diesel-PV-supercapacitor microgrid. μ -analysis shows robustness for the whole range of supercapacitor's state of charge. Experimental results on a power hardware-in-the-loop test bench are presented. Theoretical robustness analysis is confirmed by the real-time results. Abstract: This paper proposes a robust H ∞ control design approach for primary frequency regulation in a diesel-photovoltaic (PV)-storage hybrid power generation system operating in stand-alone mode. Based on real-time digital simulators, namely RT-LAB® and dSPACE®, a rapid-prototyping test bench composed of a real supercapacitor-based energy storage system (ESS) and an emulated diesel-PV-load grid is developed in order to experimentally validate this frequency control strategy under realistic operating conditions. Starting from given desired dynamic specifications, a multi-variable H ∞ controller is designed via the linear matrix inequalities (LMI) method. In the second step, uncertainty in the steady-state value of the supercapacitor state of charge ( SoC ) is considered and a robustness analysis using μ –analysis is performed in order to determine its maximum variation range for which the imposed closed-loop performances are respected for the considered operating point. MATLAB®/Simulink® time-domain simulations and real-time experiments show the effectiveness of the proposed robust control approach. Then, a series of real-time experiments are performed to validate the controller's robustness and performance in the presence of various load disturbances and SoC uncertainty.